HOW PERCEIVED RISK AND TRUST AFFECT ONLINE PAYMENT INTENTIONS: A SURVEY-BASED STUDY WITH CONFIRMATORY FACTOR ANALYSIS (CFA) AND STRUCTURAL EQUATION MODELLING (SEM) - Rahul R. Verma (Universitas Islam Negeri Raden Intan Lampung, 2025)
The rapid expansion of digital financial services has transformed transaction behaviors, yet understanding the specific drivers of purchase intention remains complex. Comprehensive literature reviews exist, there is a lack of empirical research that distinctly separates